Adult-onset hypothyroidism increases ethanol consumption - Echeverry-Alzate, V.; Buehler, K. M.; Calleja-Conde, J.; Huertas, E.; Maldonado, R.; Rodriguez de Fonseca, F.; Santiago, Catalina; Gómez-Gallego, Felix; Santos, A.; Giné, E.; López-Moreno, J. A. (Psychopharmacology, 2019)
RationaleOnly in Europe it can be estimated that more than 20 million of people would be affected by hypothyroidism in some moment of their life. Given that ethanol consumption is so frequent, it would be reasonable to ask what the consequences of ethanol consumption in those individuals affected by hypothyroidism are.ObjectivesTo study the interaction between hypothyroidism and ethanol consumption.MethodsWe study ethanol consumption in a rat model of methyl-mercaptoimidazole-induced-adult-onset hypothyroidism and thyroid T4/T3 hormone supplementation. Also, we studied the effects of ethanol on motor activity, memory, and anxiety.ResultsWe found that hypothyroidism increased the voluntary ethanol consumption and that this was enhanced by thyroid hormone supplementation. Hypothyroidism was associated with motor hyperactivity which was prevented either by T4/T3 supplementation or ethanol. The relationship between hypothyroidism, ethanol, and anxiety was more complex. In an anxiogenic context, hypothyroidism and T4/T3 supplementation would increase immobility, an anxiety-like behavior, while in a less anxiogenic context would decrease rearing, a behavior related to anxiety. Regarding memory, acute ethanol administration did not alter episodic-like memory in hypothyroid rats. Gene expression of enzymes involved in the metabolism of ethanol, i.e., Adh1 and Aldh2, were altered by hypothyroidism and T4/T3 supplementation.ConclusionsOur results suggest that hypothyroid patients would need personalized attention in terms of ethanol consumption. In addition, they point that it would be useful to embrace the thyroid axis in the study of ethanol addiction, including as a possible therapeutic target for the treatment of alcoholism and its comorbid disorders.
Keywords: hypothyroidism; alcohol; T4/T3 hormones; JCR; Scopus